A concretização da constituição tecnocientífica: o regime jurídico fundamental da ciência, tecnologia e inovação - Rodrigues, Lucas de Faria (2021)
Law, on one hand, and science, technology and innovation, on the other, are interconnected and dependent social systems. Today, science, technology and innovation undergo more intense, profound and fast transformations, at levels never before experienced in human history. Law recognizes the importance of the theme when incorporating it in the constitutional text, with two immediate consequences. Firstly, it allows the recognition of a specific fundamental right, the right to science, technology and innovation, materiallly and historically determined, made positive in the constitutional text (formal), through a dual dynamic, of apparent ambivalence, in which it contemplates a negative feature, resulting from scientific and academic freedom and a positive one, as an imposition on the State to promote and direct its development. Second, it is in the basis of a partial constitution, the Technoscientific Constitution, which object is the nation's technoscientific structure. This dogmatics is the starting point for the compatibility between a system traditionally refractory to change (Law) and another in which change is the centerpiece (science, technology and innovation), based on the understanding that both are non-neutral systems, aimed at achieving constitutionally purposes